Revision, cladistic analysis and biogeography of Typhochlaena C. L. Koch, 1850, Pachistopelma Pocock, 1901 and Iridopelma Pocock, 1901 (Araneae, Theraphosidae, Aviculariinae) - Rogerio Bertani (ZooKeys, 2012)
Three aviculariine genera endemic to Brazil are revised. Typhochlaena C. L. Koch, 1850 is resurrected, including five species; Pachistopelma Pocock, 1901 includes two species; and Iridopelma Pocock, 1901, six species. Nine species are newly described: Typhochlaena amma sp. n., T. costae sp. n., T. curumim sp. n., T. paschoali sp. n., Pachistopelma bromelicola sp. n., Iridopelma katiae sp. n., I. marcoi sp. n., I. oliveirai sp. n. and I. vanini sp. n. Three new synonymies are established: Avicularia pulchra Mello-Leitão, 1933 and Avicularia recifiensis Struchen & Brändle, 1996 are junior synonyms of Pachistopelma rufonigrum Pocock, 1901 syn. n., and Avicularia palmicola Mello-Leitão, 1945 is a junior synonym of Iridopelma hirsutum Pocock, 1901 syn. n. Pachistopelma concolor Caporiacco, 1947 is transferred to Tapinauchenius Ausserer, 1871, making the new combination Tapinauchenius concolor (Caporiacco, 1947) comb. n. Lectotypes are newly designed for Pachistopelma rufonigrum Pocock, 1901 , Iridopelma hirsutum Pocock, 1901 and Pachistopelma concolor Caporiacco, 1947. Cladistic analyses using both equal and implied weights were carried out with a matrix comprising 62 characters and 38 terminal taxa. The chosen cladogram found with X-Pee-Wee and concavity 6 suggests they are monophyletic. All species are keyed and mapped and information on species habitat and area cladograms are presented. Discussion on biogeography and conservation is provided.